Electromagnetically induced cross focusing in a four-level atomic medium - Becerra Castro, Emilio Manuel (2016)
We describe cross focusing in a four-level atomic medium under electromagnetically induced transparency. We show that due to the giant Kerr nonlinearity experienced by the atoms, cross focusing between weak signal and probe fields (both fields with intensities below line saturation level) is possible. By applying different intensity masks to the signal field, different lenses (cylindrical, Fresnel, Gaussian) can be induced in the atomic sample. Focusing of the probe beam is analyzed in terms of the excitation parameters (signal Rabi frequency and detuning, as well as optical depth of the atomic medium).